Determinación de la sustentabilidad social, económica y ambiental de la producción de la comunidad de Canchagua Chico en el periodo 2019 - 2020. - Camacho García, Karina Elizabeth (2020)
At this project agricultural farms sustainability of Canchagua Chico Community was analyzed, which has a population of 333 inhabitants, where its economy is generated by agriculture, the type of used research was documentary, quali- quantitative and analytical, with a non-experimental design, being a pioneer project in research related to analyzing production systems and living conditions of producers in mentioned area. The main objective of this project was to determine the sustainability of the agricultural producers’ farms. To carry out the work, indicators were developed in the social, economic and environmental dimensions, applying Santiago Sarandón methodology, once the surveys were carried out and the information classified, the sustainability analysis was executed using said methodology, where the following results were obtained: IG (General Index) = (IK + IE + ISC / 3) with 2.24, which indicates that there is sustainability in the sector in general, letting us know that within the economic dimension (IK) an average of 2.35 was obtained, on ecological or environmental dimension, an average of 2.38 was obtained, and at socio-cultural dimension, an average of 1.99 was obtained, which indicates that work should be done on this aspect.